First record of Oligonychus ilicis McGregor (Acari: Tetranychidae) on blueberry in Michoacan, Mexico - Esquivel-Ayala, Blanca Alicia; Vargas-Sandoval, Margarita (Revista Mexicana de Ciencias Agrícolas, 2023)
The mite also known as southern red spider or coffee spider Oligonychus ilicis is recorded for the first time in an orchard located in the town of Huaniqueo, in the municipality of Salvador Escalante, Michoacán, on three-year-old plants of Vaccinium corymbosum variety “sharp blue” detected during control sampling on October 13 and 18, 2021. The mites were found in abundance causing severe damage to the plant. This first report of O. ilicis aims to provide timely information to contain the spread of a serious phytosanitary problem.